Teacher’s Efforts to Overcome the Students’ Difficulties in Speaking Ability - Hafni Zuraida Ihsan; Nurul Wahidah (Universitas Hamzanwadi, 2018)
This study aimed at finding out the teacher’s efforts to overcome the students’ difficulties in speaking ability at the eleventh grader of high school in the school year 2017-2018. In this research there are two research question formulated as follow: What are the difficulties of the students’ in speaking ability? What are the teacher’s efforts to overcome the students’ difficulties in speaking ability? Since the study concerned on the students’ difficulties of speaking ability for the eleventh grader of high school and the teacher’s efforts to overcome the students’ difficulties in speaking ability, this research was included as a descriptive qualitative research. The subject of the study was 15 students eleventh grader of high school in the school year 2017-2018. The data in this research were collected through observation, interview and questionnaire. The result of the analysis showed that there were three kinds of the students’ difficulties in speaking ability at the eleventh grader of high school in the school year 2017-2018 that was lack of vocabulary, pronouncing the word and fluency. The teacher’s efforts to overcome the students’ difficulties in speaking ability were; asking the students to memorize the vocabulary, making English group, practicing speaking using English, and offering the students’ motivation about the importance of English.